Between paranoia and possibility: Diverse economies and the decolonial imperative. Issue 3 (10th March 2022) - Naylor, Lindsay; Thayer, Nathan
Abstract: Here we reflect on diverse economies scholarship following Gibson‐Graham's call to adopt performative practices for other worlds. Urging scholars to move from paranoia to possibility through weak theory methodology, their call provided momentum for work on economic difference that sustained critiques of capitalocentrism launched in 1996. In this clarion call to read for difference and possibility, a diverse economies framing facilitated a wholesale rejection of strong theory and paranoia. As a subdiscipline in the making, diverse economies scholars are challenged and critiqued as we seek to develop the framework and apply it to economic activities that exist within, alongside, and outside capitalism. Creating the language of diverse economies is continuous; here we consider a geopolitics of knowledge production in reading economic practice for difference, challenging the disuse of strong theory. We argue for deeper engagement with the power imbalances present in building liveable worlds, putting diverse economies and decolonial theory in conversation to address power and strike a balance between paranoia and possibility. Abstract : Arguing for a balance between the use of weak and strong theory in diverse economies scholarship, the authors put decolonial theory in conversation with diverse economies theory to examine the messy entanglements of living well.